Alternative Oxidase (AtAox) c78s Mutant Expression at Escherichia coli (SASX41DB) - Ira Djajanegara (Universitas Gadjah Mada, 2007)
Alternative oxidase (AOX) is the terminal oxidase operating in the mitochondrial electron transport chain. Theenzyme is activated by organic acid such as pyruvate and by reduction process. Based on sequences alignment ofalternative oxidase gene (Aox) found in several organisms, there are 2 conserved cysteine residues. In order toinvestigate the importance of those cysteine residues on the activity of AOX, mutation at cysteine residue number 78of Aox gene isolated from Arabidopsis thaliana (AtAox) was conducted. Cysteine at position number 78 was changedinto serine and the c78s mutant was expressed in Escherichia coli strain SASX41DB. This particular E. coli strain isunable to grow aerobically unless transformed with Arabidopsis Aox gene (AtAox). Expression studies on c78smutant showed that this mutant cannot be oxididized and can not be activated by pyruvic acid. This mutant isacivated by succinate instead of pyruvate. Mutation at cysteine closer to the N residue is affecting both organic acidand redox activation. Therefore, it is concluded that cysteine residue closer to the N residue is the site for bothactivation by pyruvate as well as activation by reduction process.Keywords : Alternative oxidase, site-directed mutation, SASx41DB, cysteine residues